Effectiveness of Growth and Development Screening and Stimulation Methods among Toddlers in Central Sulawesi, Indonesia: a Quasi-Experimental Study - Freny Ravika Mbaloto; Estelle Lilian Mua; Robi Adikari Sekeon; Alfrida Semuel Ra'bung (Poltekkes Kemenkes Palu, 2025)
Background: Stunting remains a major public health problem in Indonesia. The 2023 Indonesian Health Survey reported a stunting prevalence of 27.2% in Central Sulawesi, exceeding the national average of 21.5%. Stunting adversely affects early childhood development, yet developmental delays often go undetected due to limited developmental screening and inadequate training of health workers. This study evaluated the effectiveness of developmental screening and stimulation using the Denver Developmental Screening Test (DDST) and the Pre-Screening Developmental Questionnaire (KPSP). Methods: A quasi-experimental study with a pretest–posttest non-equivalent control group design was conducted among toddlers (n = 34). Nutritional status was assessed using anthropometric z-scores, while child development was evaluated using the DDST and KPSP instruments. Children who were ill, had physical disabilities, or had diagnosed developmental disorders were excluded. Data were analyzed using Pearson chi-square, Mann–Whitney, and Wilcoxon tests. Results: A significant difference in nutritional status proportions between groups was identified based on anthropometric screening (p = 0.036). Developmental screening scores differed significantly between DDST and KPSP assessments (p = 0.001), with higher mean ranks observed for KPSP. Post-stimulation analysis demonstrated a significant improvement in KPSP scores compared to pre-stimulation results (p = 0.009), indicating the positive effect of developmental stimulation. Conclusion: Developmental screening and stimulation significantly improved developmental outcomes in toddlers. The KPSP demonstrated higher sensitivity in detecting developmental changes compared to the DDST, supporting its use in community-based child development monitoring.